Metabolic Characterization of Supernatants Produced by Lactobacillus spp. With in vitro Anti-Legionella Activity - Fuochi, Virginia; Coniglio, Maria Anna; Laghi, Luca; Rescifina, Antonio; Caruso, Massimo; Stivala, Aldo; Furneri, Pio Maria (Frontiers in Microbiology, 2019)
Legionella pneumophila is an organism of public health interest for its presence in water supply systems and other humid thermal habitats. In this study, ten cell-free supernatants produced by Lactobacillus strains were evaluated for their ability to inhibit L. pneumophila strains isolated from hot tap water. Production of antimicrobial substances by Lactobacillus strains were assessed by agar well diffusion test on BCYE agar plates pre-inoculated with L. pneumophila. Cell-free supernatants (CFS) showed antimicrobial activity against all Legionella strains tested: L. rhamnosus and L. salivarius showed the highest activity. By means of a proton-based nuclear magnetic resonance (1H-NMR) spectroscopy, we detected and quantified the Lactobacillus metabolites of these CFSs, so to gain information about which metabolic pathway was likely to be connected to the observed inhibition activity. A panel of metabolites with variations in concentration were revealed, but considerable differences among inter-species were not showed as reported in a similar work by Foschi et al.(2018). More than fifty molecules belonging mainly to the groups of amino acids, organic acids, monosaccharides, ketones and alcohols were identified in the metabolome. Significant differences were recorded comparing the metabolites found in the supernatants of strains grown in MRS with glycerol and the same strains grown in MRS without supplements. Indeed, pathway analysis revealed that glycine, serine and threonine, pyruvate and sulfur metabolic pathways had a higher impact when strains were grown in MRS medium with a supplement such as glycerol. Among the metabolites identified, many were amino acids, suggesting the possible presence of bacteriocins which could be linked to the anti-Legionella activity shown by cell-free supernatants.